Xuedan Sustained Release Pellets Ameliorate Dextran Sulfate Sodium–Induced Ulcerative Colitis in Rats by Targeting Gut Microbiota and MAPK Signaling Pathways - Zhang, Yingchun; Feng, Dan; Zeng, Yue; Zhang, Hanyu; Du, Xiaohong; Fu, Yang; Wang, Xinhui; Lian, Dingyue; Wang, Ruikang; Xiao, Hongyu; Wei, Ning; Zhai, Fuqiang; et al. (Frontiers in Pharmacology, 2022)
Cucurbitacins have a variety of bioactivities, such as anticancer, anti-inflammatory, antidepressant-like, and antiviral effects, but their pharmacological effect in ulcerative colitis (UC) has not been reported until now. Thus, this study aims to investigate the preventive effects of Xuedan sustained release pellets (XSPs) on UC rats and the underlying mechanisms. XSPs were prepared by extracting cucurbitacins from Hemsleya. Experimental UC rats were induced by the intake of 4% dextran sulfate sodium (DSS) for a week and treated with different doses of XSP (0.95, 1.90, and 3.8 mg/kg). The body weight, colon length, disease activity index (DAI), and histological changes of colonic tissue were measured. In addition, the expressions of pro-inflammatory cytokines were detected by using the enzyme-linked immunosorbent assay. Pathways involved in the intestinal inflammation were targeted by RNA-sequencing. Moreover, the changes of gut microbial diversity and composition were analyzed by the 16SrNA analysis and the contents of short-chain fatty acids (SCFAs) were detected by GC-MS. The results revealed that XSP intervention greatly restored the weight loss and colonic shortening (p < 0.05) and reduced the raised DAI scores, myeloperoxidase, and nitric oxide activities in UC in rats (p < 0.05). XSP administration also downregulated the protein levels of pro-inflammatory factors IL-1β, IL-6, and TNF-α. Notably, it was found that XSP considerably suppressed the activation of the MAPK signaling pathway. In addition, XSP treatment improved the balance of gut microbiota that was disturbed by DSS. The beneficial bacteria Lachnospiraceae_NK4A136 group and Lactobacillus at the genus level significantly increased in the XSP group, which had decreased with the use of DSS (p < 0.05). Pathogenic bacteria including Escherichia–Shigella and Bacteroides in UC in rats were reduced by XSP intervention. Furthermore, XSP significantly elevated the production of SCFAs in UC in rats (p < 0.05). These alterations in inflammatory status were accompanied with changes in gut microbiota diversity and SCFA production. In conclusion, XSP exhibited protective effects against DSS-induced UC in rats. XSP treatment decreased inflammation via modulation of gut microbiota composition and SCFA production.